A low power 35 GHz CMOS high linearity, unconditional stability and excellent gain flatness UWB power amplifier design using current reused technique. (2015) - Bhale, Vishakha; Dalal, Upena
A two-stage 0.18 µm RF CMOS current reused class-AB power amplifier design is proposed for 35 GHz ultra-wide-band application. It uses a cascade with current reused as first stage and common source with resistive feedback as a second stage. The simulation results shows a gain flatness of 24 dB and an input 1 dB compression of −14.63 dBm while consuming 22.6 mW of power from 1.8 V supply. Further, the input and output return loss of less than −9 dB and −15 dB respectively is obtained and reverse isolation of less than −58 dB provides good port to port isolation. The efficiency of the designed power amplifier is 24% at an input RF power of −5 dBm. Unconditional stability, good linear and low power consumption is the novelty of the proposed PA design with a considerable group delay of ± 550 pS.